Análisis de riesgos en proyectos de inversión - Sánchez Z., Elias (2009)
In almost all private projects, we use concepts like demand, supply, risk aversion, etc. although, just a few times, we observes the application of instruments properly related to the economic analysis to evaluate these projects. The experiences obtained in my professional life let me verify the importance of the economic instruments for measuring the impact of the degree of aversion to the risk decision-maker in particular, and the risk analysis, in general. To scarce resources, high uncertainty and few alternative of election, there is a high certainty in the decisions; however, they are rarely used for their “complicated” aplication, perception that we intend to reduce with this article.